Modality in spoken Malaysian English : a comparison with the supervarieties - Ang, Leng Hong; He, Mengyu; Hajar Abdul Rahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
The interest in Malaysian English generated many studies on Malaysian English focusing on various grammatical features. However, modality in Malaysian English is still under-researched, especially in post-independence and new Englishes contexts. As a new variety of English, it raises questions on how Malaysian English has developed from the historical input variety, i.e., British English and how resistant or accepting Malaysian English is to American English which is highly influential globally. This study aimed to contribute to the development of Malaysian English studies by reporting a corpus-based research of the frequency and statistical differences of a set of modal and quasi-modal verbs in three spoken corpora representing Malaysian, British, and American English. AntConc software (Version 3.5.9) (Anthony, 2020) was used to explore and generate the relevant data in the spoken Malaysian English corpus, while the spoken British and American English corpora were accessed online using the tools on the respective websites. The findings show that the use of modal and quasi-modal verbs in spoken Malaysian English does not entirely resemble either of the Supervarieties, i.e., spoken British English and American English. Log-likelihood test carried out in the study shows significant differences in the use of certain modal and quasi-modal verbs between the varieties, suggesting that Supervarieties are not always in the lead in using quasi-modals. The results also suggest that these significant differences are mainly accounted for by the nativisation process and evolution of Malaysian English as a new English variety. The findings shed new light on the current knowledge of modal and quasi-modal verbs in post-independence spoken Malaysian English.